2015
DOI: 10.13005/bpj/600
|View full text |Cite
|
Sign up to set email alerts
|

New Naphthalene-Derivative as Cardioprotector Drug on the Ischemia/Reperfusion Injury

Abstract: There is scarce information about the effects exerted by the naphthalene derivatives on cardiac injury caused by ischemia/reperfusion. In this study, a new naphthalene derivative was synthetized with the objective of evaluating its activity on ischemia/reperfusion injury.The Langendorff technique was used to evaluate the effect of the naphthalene derivative on ischemia/reperfusion injury. Additionally, molecular mechanism involved in the activity exerted by the naphthalene derivative on perfusion pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Alternative experiments were carried out to determine whether increases in the dose (0.001 to 100 nM) of 4-Me-7-Ph-C could produce changes in the infarct size; the results indicated that coumarin derivative decreased infarct area in a dose-dependent manner compared with the control vehicle. This phenomenon could be achieved through changes in perfusion pressure, a hypothesis supported by other studies indicating that some compounds can exert changes in perfusion pressure [30,31]. Analyzing our data, the biological activity produced by 4-Me-7-Ph-C on perfusion pressure was determined using an isolated rat heart model.…”
Section: Discussionsupporting
confidence: 75%
“…Alternative experiments were carried out to determine whether increases in the dose (0.001 to 100 nM) of 4-Me-7-Ph-C could produce changes in the infarct size; the results indicated that coumarin derivative decreased infarct area in a dose-dependent manner compared with the control vehicle. This phenomenon could be achieved through changes in perfusion pressure, a hypothesis supported by other studies indicating that some compounds can exert changes in perfusion pressure [30,31]. Analyzing our data, the biological activity produced by 4-Me-7-Ph-C on perfusion pressure was determined using an isolated rat heart model.…”
Section: Discussionsupporting
confidence: 75%